Development of Automated Separation, Expansion, and Quality Control Protocols for Clinical-Scale Manufacturing of Primary Human NK Cells and Alpharetroviral Chimeric Antigen Receptor Engineering - Oberschmidt, Olaf (Hum Gene Ther Methods, 2019)
In cellular immunotherapies, natural killer (NK) cells often demonstrate potent antitumor effects in high-risk cancer patients. But Good Manufacturing Practice (GMP)-compliant manufacturing of clinical-grade NK cells in high numbers for patient treatment is still a challenge. Therefore, new protocols for isolation and expansion of NK cells are required. In order to attack resistant tumor entities, NK cell killing can be improved by genetic engineering using alpharetroviral vectors that encode for chimeric antigen receptors (CARs). The aim of this work was to demonstrate GMP-grade manufacturing of NK cells using the CliniMACS(®) Prodigy device (Prodigy) with implemented applicable quality controls. Additionally, the study aimed to define the best time point to transduce expanding NK cells with alpharetroviral CAR vectors. Manufacturing and clinical-scale expansion of primary human NK cells were performed with the Prodigy starting with 8-15.0 × 10(9) leukocytes (including 1.1–2.3 × 10(9) NK cells) collected by small-scale lymphapheresis (n = 3). Positive fraction after immunoselection, in-process controls (IPCs), and end product were quantified by flow cytometric no-wash, single-platform assessment, and gating strategy using positive (CD56/CD16/CD45), negative (CD14/CD19/CD3), and dead cell (7-aminoactinomycine [7-AAD]) discriminators. The three runs on the fully integrated manufacturing platform included immunomagnetic separation (CD3 depletion/CD56 enrichment) followed by NK cell expansion over 14 days. This process led to high NK cell purities (median 99.1%) and adequate NK cell viabilities (median 86.9%) and achieved a median CD3+ cell depletion of log −3.6 after CD3 depletion and log −3.7 after immunomagnetic CD3 depletion and consecutive CD56 selection. Subsequent cultivation of separated NK cells in the CentriCult(®) chamber of Prodigy resulted in approximately 4.2–8.5-fold NK cell expansion rates by adding of NK MACS(®) basal medium containing NK MACS(®) supplement, interleukin (IL)-2/IL-15 and initial IL-21. NK cells expanded for 14 days revealed higher expression of natural cytotoxicity receptors (NKp30, NKp44, NKp46, and NKG2D) and degranulation/apoptotic markers and stronger cytolytic properties against K562 compared to non-activated NK cells before automated cultivation. Moreover, expanded NK cells had robust growth and killing activities even after cryopreservation. As a crucial result, it was possible to determine the appropriate time period for optimal CAR transduction of cultivated NK cells between days 8 and 14, with the highest anti-CD123 CAR expression levels on day 14. The anti-CD123 CAR NK cells showed retargeted killing and degranulation properties against CD123-expressing KG1a target cells, while basal cytotoxicity of non-transduced NK cells was determined using the CD123-negative cell line K562. Time-lapse imaging to monitor redirected effector-to-target contacts between anti-CD123 CAR NK and KG1a showed long-term effector–target interaction. In conclusion, the integration of the clinical-scale expansion procedure in the automated and closed Prodigy system, including IPC samples and quality controls and optimal time frames for NK cell transduction with CAR vectors, was established on 48-well plates and resulted in a standardized GMP-compliant overall process.